Anmeldelser - Finscher, Ludwig (Danish Yearbook of Musicology, 1992)
Review of: Dania Sonans V. Musik fra Christian lIIs tid. Udvalgte satser fra det danske hojkapels stemmebøger (1541). Anden og tredje del. Udgivet af Henrik Glahn. Music from the Time of Christian III. Selected Compositions from the Part Books of the Royal Chapel (1541). Part Two and Three. Edited by Henrik Glahn. Edition Egtved (1986).